2009
DOI: 10.1007/s11426-009-0251-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of La3+ and Eu3+ on outward potassium channels in Vicia guard cells

Abstract: Effects of La 3+ and Eu 3+ on outward potassium channels (K + out ) in Vicia guard cells have been studied by patch clamping technique. Extracellular La 3+ inhibited K + out currents with a half-inhibition concentration (IC 50 ) of 81 μmol·L −1 . Interestingly, intracellular La 3+ activated K + out currents at a free concentration of 1.13 × 10 −14 mol·L −1 , and inhibited K + out currents at a free concentration of 5.86 × 10 −14 mol·L −1 . Extracellular Eu 3+ also activated K + out currents at concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The role played during REE exploitation in agricultural practices carried out in China is justified by the capability of these elements to favour some metabolic processes leading to increases in plant productivity, by modifying, for example, stomatal openings and regulating transpiration and water depletion through plant leaves (Schroeder et al, 2001). Recent studies offer evidence for the ability of Eu 3+ to intervene on the outward K + channels of Vicia guard cells and consequently regulating the cell water contents (Xue and Yang, 2009).…”
Section: Aerial Portionsmentioning
confidence: 99%
“…The role played during REE exploitation in agricultural practices carried out in China is justified by the capability of these elements to favour some metabolic processes leading to increases in plant productivity, by modifying, for example, stomatal openings and regulating transpiration and water depletion through plant leaves (Schroeder et al, 2001). Recent studies offer evidence for the ability of Eu 3+ to intervene on the outward K + channels of Vicia guard cells and consequently regulating the cell water contents (Xue and Yang, 2009).…”
Section: Aerial Portionsmentioning
confidence: 99%
“…The influence of Ln 3+ on channels in non-excitable cells has not been sufficiently investigated. Xue et al [23] showed the effect of La 3+ on outward potassium channels in Vicia guard cells. We previously studied the effects of Yb 3+ on potassium current in non-excitable NIH3T3 cells [24].…”
Section: Introductionmentioning
confidence: 99%